Atrial fibrillation ablation in a patient complicated by persistent left superior vena cava and absent right superior vena cava. Issue 2 (9th February 2022) - Takenaka, Sou; Enzan, Ayano; Ueno, Akihiko; Sakakibara, Masayoshi
Abstract : A comparison between the three‐dimensional contact mapping created by the Ensite system and that created by contrast‐enhanced computed tomography angiography (CTA). Right atrial appendage was not well delineated on CTA.